The study of quaternary semiconducting chalcogenide nanomaterials for application as counter electrodes - Ngubeni, Grace Nomthandazo (University of the Witwatersrand, Johannesburg, 2021)
Herein, the colloidal synthesis of Cu2ZnSnS4 (CZTS), Cu2ZnSnSe4 (CZTSe) and the first time colloidal synthesis of Li2ZnSnS4 (LZTS) and Na2ZnSnS4 (NZTS) nanoparticles respectively were investigated. All the nanoparticles were applied as counter electrodes in dye-sensitized solar cells (DSSCs). For the CZTS and CZTSe nanoparticles in particular, the effect of three substrates, namely, vitreous carbon (VC), indium tin oxide (ITO) and fluorine doped tin oxide (FTO) on the electrocatalytic properties including the overall performance of the solar cells were investigated. The CZTS and CZTSe were successfully synthesized and characterized with X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared (FT-IR), nuclear magnetic resonance (NMR), and ultra-violet visible (UV-vis) spectroscopy and transmission electron microscope (TEM) for the morphologies. CZTSe on glassy carbon (VC) had better electrocatalytic activity as compared to CZTS, however, the DSSCs from VC were poor due to the reduced transmittance of the substrate. On ITO and FTO, CZTS performed the best. Electrochemically, CZTS had the lowest series resistance and charge transfer resistance however had the largest exchange current density and limiting diffusion current thereby making it the best electrocatalyst. The DSSC using CZTS–ITO gave the best performance with the power conversion efficiency (PCE) of 3.62%. Conversely, for the LZTS and NZTS nanoparticles the effect of the lithium and sodium precursors and the ratio of the constituents e.g. Li:Zn:Sn:S and Na:Zn:Sn:S on the properties of the LZTS and NZTS nanoparticles, respectively were investigated. In addition, the effect of the substrates, that is, ITO vs FTO on the electrocatalytic properties as well as overall performance of the DSSCs were studied. Using the Li2S precursor, the XPS, 7Li MAS NMR and Raman spectroscopy confirmed the presence of lithium and the formation of LZTS. Since the Li2S source and the 2:1:0.25:2 ratio, resulted in the purest particles, these were therefore used as CEs in DSSCs for the first time. LZTS nanoparticles on ITO gave the best performance with 2.26% PCE. Similarly, the study of NZTS indicated that the NaCl regardless of the ratios used resulted in the formation of impurities as observed from XRD patterns. The presence of sodium and the complete formation of NZTS nanoparticles through 23Na MAS NMR, XPS and Raman v spectroscopy were investigated. The results indicated that the Na2S-based nanoparticles in the 2:1:0.5:4 ratio, yielded the purest NZTS nanoparticles. As such, these results indicated a PCE of 3.93%. The study illustrates that alkali metals (Li+ and Na+) can be used as the monovalent cation in quaternary nanoparticles, instead of the commonly used Cu+ transition metal with promising results as counter electrode materials in DSSCs. Notably, the NZTS nanoparticles illustrated a higher PCE to CZTS while LZTS had the lowest PCE. It must be however noted, that these results require further optimization to explore the full potential of these alkali metal-based quaternary nanoparticles.
A research report submitted in fulfillment of the requirements for the Master of Doctor of Philosophy, In the Faculty of Commerce, Law and Management, School of Chemistry, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Cu2ZnSnS4; Cu2ZnSnSe4; Li2ZnSnS4; Na2ZnSnS4; substrates; counter electrodes; dye-sensitized solar cells; SDG-7: Affordable and clean energy; SDG-9: Industry, innovation and infrastructure